A Gentle Introduction to the Art of Mathematics: Version 2.0 - Fields, Joseph (Lulu, 2010)
Keywords: Mathematics; Textbooks; dept.mat

Cohen–Macaulayness versus the vanishing of the first Hilbert coefficient of parameter ideals - Ghezzi, Laura; Goto, Shiro; Hong, Jooyoun; Ozeki, Kazuho; Phuong, Tran Thi; Vasconcelos, Wolmer V (Journal of The London Mathematical Society-second Series, 2010)
The conjecture of Wolmer Vasconcelos on the vanishing of the first Hilbert coefficient e1(Q) is solved affirmatively, where Q is a parameter ideal in a Noetherian local ring. Basic properties of the rings for which e 1(Q) vanishes are derived. The invariance of e1(Q) for parameter ideals Q and its relationship to Buchsbaum rings are studied. © 2010 London Mathematical Society.
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/176-080-348-377-227 tex.type: [object Object]
Keywords: dept.mat

The positivity of the first coefficients of normal Hilbert polynomials - Goto, Shiro; Hong, Jooyoun; Mandal, Mousumi (Proceedings of the American Mathematical Society, 2010)
Let R be an analytically unramified local ring with maximal ideal m and d = dimR > 0. If R is unmixed, then e1I (R) = 0 for every m-primary ideal I in R, where e1I (R) denotes the first coefficient of the normal Hilbert polynomial of R with respect to I. Thus the positivity conjecture on e1I(R) posed by Wolmer V. Vasconcelos is settled affirmatively. © 2010 American Mathematical Society.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/045-772-863-857-214
Keywords: Associated graded ring; Normal Hilbert polynomial; Normal ideal; Rees algebra; dept.mat

Academic freedom and tenure: Clark atlanta university - Williams, Rebecca J; Betsey, Charles L; Gasman, Marybeth; Grant, Kerry; Rabban, David M (Academe, 2010)
Citation Key Alias: lens.org/095-837-567-108-858
Keywords: dept.mat; ⛔ No DOI found

Trends in alcohol consumption among undergraduate students at a northeastern public university, 2002-2008. - Bulmer, Sandra Minor; Irfan, Syed; Mugno, Raymond; Barton, Barbara; Ackerman, Louise (Journal of American college health : J of ACH, 2010)
OBJECTIVE: This study examined alcohol consumption patterns and trends at a public university in the Northeast from 2002 to 2008., PARTICIPANTS: Stratified random sampling was used to select undergraduate students enrolled in courses during spring semesters in 2002, 2004, 2006, and 2008., METHODS: Data were collected during regularly scheduled classes for 4 measures of alcohol consumption and 5 demographic categories using the Core Alcohol and Drug Survey., RESULTS: Four groups showed significant increases in both frequency and volume of alcohol consumption-students who were female, over 21 years of age or over, living off-campus, or performing well academically. There were no decreasing trends for any demographic group. These results differ from national college health surveys, which have shown alcohol use remaining steady during this period., CONCLUSIONS: Campus-specific trend data can provide unique perspectives and guide programming efforts. These trends suggest a need for new intervention strategies on this campus.
7 citations (Crossref) [2023-10-31] Place: United States Bulmer, Sandra Minor. Department of Public Health, Southern Connecticut State University, New Haven, Connecticut 06515, USA. bulmers1@southernct.edu
Keywords: *Alcohol Drinking/ep [Epidemiology]; *Public Sector/sn [Statistics & Numerical Data]; *Students/sn [Statistics & Numerical Data]; *Universities/sn [Statistics & Numerical Data]; Alcohol Drinking; Alcohol consumption; College; Connecticut; Data Collection; Drinking; Female; Humans; Male; Public Sector; Risk-Taking; Statistics; Nonparametric; Students; Trends; United States; Universities; Young Adult; adult; article; dept.mat; dept.pch; drinking behavior; female; high risk behavior; human; information processing; male; nonparametric test; organization and management; peer-reviewed; statistics; student; university